(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
Humans naturally interface transparently with tools, thus extending through them. Advancing technology has finally produced tools that begin to match our capacities, integrating them more transparently with our minds. We move from tool users towards cybernetic minds, taking our unique human neuroplasticity to the next level.